Sandiwara Daerah of Radio Republik Indonesia Yogyakarta and Surakarta, 1950s-1990s - Dhanang Respati Puguh; Rafngi Mufidah (Department of History, Faculty of Humanities, Diponegoro University, 2020)
This article discusses Sandiwara Daerah [regional plays] organized by Radio Republik Indonesia Yogyakarta and Surakarta by applying historical method. This article shows that Sandiwara Daerah broadcasts on Radio Republik Indonesia (RRI) Yogyakarta and Surakarta had been held since the 1950s. The performance of Sandiwara Daerah broadcast profoundly related to the position of RRI as a government cultural media which exclusively responsible for disseminating regional cultures. Sumardjono and Maria Kadarsih are prominent figures in the production process of Sandiwara Daerah RRI Yogyakarta, as well as Siti Aminah who became a key figure in the production process of Sandiwara Daerah RRI Surakarta. Sandiwara Daerah is an event favored by the Javanese people. Nevertheless, Sandiwara Daerah experienced a decline since the private radios launched Sandiwara Radio in 1990.